Anatomy, nutritional value and cell wall chemical analysis of foliage leaves of Guadua chacoensis (Poaceae, Bambusoideae, Bambuseae), a promising source of forage - Panizzo, Cecilia Clara (2017)
Fil: Panizzo, Cecilia Clara. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Recursos Naturales y Ambiente. Cátedra de Botánica General. Buenos Aires, Argentina.